Aspen plus simulation model of municipal solid waste gasification of metropolitan city for syngas production. (15th July 2023) - Mehdi, Muzaffar; Ammar Taqvi, Syed Ali; Shaikh, Asif Ahmed; Khan, Saad; Naqvi, Salman Raza; Shahbaz, Muhammad; Juchelková, Dagmar
Highlights: Aspen Plus based simulation model for steam gasification of municipal solid waste. Increase in temperature from 700 °C to 1300 °C increased the concentration of H2 increased from 37 to 51 mol%. The H2 concentration increased from 34 to 44 mol% by increasing the steam to MSW ratio from 0.05 to 0.8 mass fraction. Increase in air to MSW ratio from 0.01 to 0.5 mass fraction the H2 concentration decreases from 47 to 39 mol% but peaks at 0.05 at which it is 48 mol%. Abstract: It is apparent that the population, in general, is increasing and this rise in population increases both the waste production and energy requirements. The main objective of this study to tackle the increasing demand for energy and recycling waste into energy. We will be using Waste to Energy (WTE) technique to convert MSW into energy such as bio-fuel, Hydrogen-rich gas or Syngas. The model of simulation of steam gasification of MSW used in this study is based on ASPEN PLUS. Temperature, the ratio of steam to MSW, and the ratio of air to MSW have all been adjusted in a wide range. For the production of syngas, the impact of carbon conversion efficiency (CCE) and cold gas efficiency (CGE) has been studied. The results showed that by increasing the temperature from 700 °C to 1300 °C the H2 concentration increased from 37 to 51 mol%, CO concentration increases from 35 to 40 mol% and CO2 concentration decreases from 5 to 0.025 mol%. CGE also decreases from 95 to 82% while CCE increases from 80 to 85%. By increasing the steam to MSW ratio from 0.05 to 0.8 mass fraction the H2 concentration increased from 34 to 44 mol% but is maximum at 0.35 at which it is 53 mol%, CO concentration decreases from 43 to 16 mol% and CO2 concentration increases from 0.025 to 8.5 mol%. CGE and CCE also decreases from 94 to 45% and 90 to 44% respectively.And lastly by increasing the air to MSW ratio from 0.01 to 0.5 mass fraction the H2 concentration decreases from 47 to 39 mol% but peaks at 0.05 at which it is 48 mol%, CO concentration decreases from 41 to 31 mol% and CO2 concentration increases from 0.085 to 3.5 mol%. CGE and CCE also decreases from 92 to 55% and 87 to 70% respectively. To compare our data with the base case we have kept temperature at 900 °C S/MSW ratio at 0.11 and air/MSW ratio at 0.05 and it is concluded that our simulation is inline with the base case as our results are off by just 1–3% in terms of yield.